Improved delivery of sinus irrigations after middle turbinate resection during endoscopic sinus surgery. Issue 4 (9th December 2016) - Kidwai, Sarah M.; Parasher, Arjun K.; Khan, Mohemmed N.; Eloy, Jean Anderson; Del Signore, Anthony; Iloreta, Alfred Marc; Govindaraj, Satish
Abstract : Background: Improvement in topical delivery to nasal mucosa is a fundamental goal of endoscopic sinus surgery (ESS). This study compares the penetration of irrigation before and after middle turbinate resection (MTR) to assess the efficacy of topical delivery. Methods: ESS was performed on 4 cadaver heads, followed by MTR. Each head was irrigated with fluorescein‐dyed water using a squeeze bottle both before and after MTR. Videos were recorded by rigid nasal endoscopy. Four blinded raters reviewed videos and scored the extent of staining (0 to 3) for each site. Results: The mean score for the extent of staining of all anatomical sites before and after MTR was 1.30 and 1.92, respectively ( p = 0.035). The mean score for extent of staining before and after MTR was 2.56 and 2.81 ( p = 0.134) for the maxillary sinus, 1.66 and 2.25 ( p = 0.022) for the ethmoid sinus, 1.03 and 1.94 ( p = 0.263) for the sphenoid sinus, 0.16 and 0.94 ( p = 0.055) for the frontal sinus, and 1.09 and 1.66 ( p = 0.340) for the olfactory cleft, respectively. When evaluating interrater reliability, Cronbach's alpha was 0.92, which is acceptable. When evaluating intrarater reliability, the Fleiss kappa statistic for each rater was excellent or good. Conclusion: Overall, MTR results in significant improvement in the penetration of nasal irrigations in the cadaver model. Each individual sinus displays a trend toward improvement; however, only the ethmoid sinus displays a statistically significant improvement. Further in vivo studies are needed to elucidate the role of MTR.